Characteristics, efficacy, and prognosis analysis of newly diagnosed marginal zone lymphoma - Wang, Haotian; Zhang, Ying; Li, Zhaoxia; Bai, Ou (Frontiers in Immunology, 2024)
Objective To retrospectively analyze the characteristics of newly diagnosed marginal zone lymphoma (MZL) patients, evaluate the efficacy of different treatment regimens, and explore prognostic factors in the era of immunotherapy. Methods We reviewed the clinical data of newly diagnosed MZL patients treated at the Department of Hematology, The First Hospital of Jilin University, from October 2013 to October 2023. Survival differences between groups were analyzed using the log-rank test, and prognostic factors were identified. Results A total of 265 newly diagnosed MZL patients were included, with a median age of 59 years (range 22-90). The most common pathological type was mucosa-associated lymphoid tissue (MALT) lymphoma, accounting for 66.0% of cases. Among the 147 MZL patients included in the efficacy analysis, the median follow-up was 43.4 months. Both the median progression-free survival (PFS) and overall survival (OS) were not reached. The 5-year PFS and OS rates were 76.0% and 86.6%, respectively. Patients who achieved complete response (CR) after induction therapy had significantly better PFS (P=0.0045), OS (P<0.001), and time to next treatment (TTNT) (P=0.0045) compared to those who did not achieve CR. A subgroup analysis was conducted on 51 MZL patients with high tumor burden who received ≥4 cycles of treatment. It was found that the CR rate (CRR) in patients receiving obinutuzumab (G) ± chemotherapy was significantly higher than in those receiving rituximab (R) ± chemotherapy (93.8% vs. 48.6%, P=0.002). Multivariate analysis revealed that disease progression or death within 24 months of initial treatment (POD24) was an independent risk factor affecting OS (P<0.001). Patients who experienced POD24 had a median survival of only 19.7 months, with a 3-year OS rate of just 37.6%, whereas those without POD24 had a 3-year OS rate of 97.3%. Conclusion MZL is predominantly seen in middle-aged and elderly patients and is a specific indolent B-cell lymphoma, with MALT lymphoma being the most common subtype. Achieving CR after induction therapy significantly prolongs survival in MZL patients. Compared to R ± chemotherapy, G ± chemotherapy achieves a higher CRR in high tumor burden MZL patients. In the era of immunotherapy, POD24 is an independent prognostic factor for MZL.